Penolakan Amerika Serikat Atas Usaha Kemerdekaan Ossetia Selatan Tahun 2008 - Rahmat Fanani Prasetya (HI 16 UMY 154, 2016)
After Soviet Union collapsed, Georgia declared its independence. Ossetians were divided into two regions which are South Ossetia and North Ossetia. North Ossetia is located in Russia region and South Ossetia is located in Georgia region. Civil war started between Georgia and South Ossetia caused by discriminative policy. South Ossetia decided to gain their independence by starting their separatist movement. It led to United States involvement in the conflict region.